Inkarnasi Yesus Sebagai Paradigma Kepemimpinan Gereja - Awuy, Alfina Aprilla; Tombeng, Ineke Marlien (Institut Injil Indonesia, 2025)
Church leadership is often reduced to structural or administrative aspects, whereas theologically it is a calling to embody the love, power, and character of Christ among His people. This study is grounded in the theology of incarnation, particularly John Calvin’s perspective within the Reformed theological framework, which emphasizes that Jesus Christ, as God who became human, is the ultimate model of leadership. The aim of this research is to formulate a church leadership paradigm rooted in incarnational principles, enabling church leaders to serve with humility, solidarity, and transformative impact. The research method employed is a literature study with a theological-doctrinal approach, examining biblical sources, Calvin’s works, and contemporary literature on Christian leadership. The findings reveal that incarnational leadership requires the leader’s full engagement with the congregation, willingness to empathize with their struggles, and commitment to holistic restoration. This paradigm is relevant not only to pastoral ministry but also as a model for church leadership amid today’s complex challenges. Thus, church leadership grounded in the example of Jesus’ incarnation can foster authentic, edifying, and transformative ministry for the spiritual and social renewal of the congregation.